Pengaruh Strategi Marketing E-Commerce Shopee Dan Media Tiktok Dalam Perspektif Nilai Edukasi - Evi, Margaretha; Dewi, Lisa Octavia Apliana; Amarjupi, Dela Sheren (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
The purpose of this study is to find out the marketing strategies carried out by the shopee marketplace in increasing shopping convenience and trust as well as repeat purchase decisions so that they are able to compete with the presence of the current TikTok social media application in Indonesia. In addition to the function of this application is to create interesting video content, this application can also be used as a product sales promotion tool through promotional videos. Viewed from the educational aspect, the Tiktok application can affect the mental and moral of children and adolescents, this is a polemic for parents. This research method uses quantitative methods by utilizing path analysis and Sobel test using a questionnaire as a primary data collection tool. The subjects in this study were internet users, totaling 50 respondents from factory employees in Central Java. The results show that the market strategy at Shopee has a very significant influence on the level of trust and convenience of online shopping, and is also influenced by price promotions, product quality and reviews from users can strengthen shopee's existence to date and the presence of the Tiktok application does not affect the decline. shopee loyal user intensity level.